Selection of a novel cell-internalizing RNA aptamer specific for CD22 antigen in B cell acute lymphoblastic leukemia - Dario Ruiz-Ciancio; Li-Hsien Lin; Suresh Veeramani; Maya N. Barros; Diego Sanchez; Ary Lautaro Di Bartolo; Diego Masone; Paloma H. Giangrande; María Belén Mestre; William H. Thiel (Elsevier, 2023)
Despite improvements in B cell acute lymphoblastic leukemia (B-ALL) treatment, a significant number of patients experience relapse of the disease, resulting in poor prognosis and high mortality. One of the drawbacks of current B-ALL treatments is the high toxicity associated with the non-specificity of chemotherapeutic drugs. Targeted therapy is an appealing strategy to treat B-ALL to mitigate these toxic off-target effects. One such target is the B cell surface protein CD22. The restricted expression of CD22 on the B-cell lineage and its ligand-induced internalizing properties make it an attractive target in cases of B cell malignancies. To target B-ALL and the CD22 protein, we performed cell internalization SELEX (Systematic Evolution of Ligands by EXponential enrichment) followed by molecular docking to identify internalizing aptamers specific for B-ALL cells that bind the CD22 cell-surface receptor. We identified two RNA aptamers, B-ALL1 and B-ALL2, that target human malignant B cells, with B-ALL1 the first documented RNA aptamer interacting with the CD22 antigen. These B-ALL-specific aptamers represent an important first step toward developing novel targeted therapies for B cell malignancy treatments.